2015
DOI: 10.1177/1362361315577218
|View full text |Cite
|
Sign up to set email alerts
|

Use of early intervention for young children with autism spectrum disorder across Europe

Abstract: Little is known about use of early interventions for autism spectrum disorder (ASD) in Europe. Parents of children with ASD aged 7 years or younger (N=1680) were recruited through parent organisations in 18 European countries and completed an online survey about the interventions their child received. There was considerable variation in use of interventions and in some countries more than 20% of children received no intervention at all. The most frequently reported treatments were speech and language therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 38 publications
5
73
2
3
Order By: Relevance
“…This indirect endorsement of ABA by Howlin et al is misleading because in fact, only one third (32.3 %) of young children with ASD (aged <6 years) in Europe are reported to receive behavioural intervention of any type, with estimates ranging from 8.6 % in the Czech Republic to 80.6 % in Romania (Salomone et al 2014). Salomone et al found that the average number of hours per week was 8.69 (range 0.64-23.00; SD 9.80).…”
Section: Gulf Between Europe and North Americamentioning
confidence: 99%
“…This indirect endorsement of ABA by Howlin et al is misleading because in fact, only one third (32.3 %) of young children with ASD (aged <6 years) in Europe are reported to receive behavioural intervention of any type, with estimates ranging from 8.6 % in the Czech Republic to 80.6 % in Romania (Salomone et al 2014). Salomone et al found that the average number of hours per week was 8.69 (range 0.64-23.00; SD 9.80).…”
Section: Gulf Between Europe and North Americamentioning
confidence: 99%
“…A recent study surveyed the use of early intervention for young children with autism spectrum disorders across 18 European countries. It found that, in Europe as a whole, speech and language therapy was the most frequently provided intervention for young children with autism, received by 64% of children; in comparison, only 22% of Danish children received speech and language therapy, the second lowest percentage in the 18 European countries (Salomone et al, 2015).…”
Section: Clinical Implications Of Assumptionmentioning
confidence: 99%
“…However, the Danish approach differs from community standards in other European countries as well as in the United States, where verbal language is included as an important target for early intervention (e.g., TagerFlusberg et al, 2009;Virués-Ortega, 2010;Salomone et al, 2015), and speech-language pathologists are central to the early intervention process (Smith & Dillenbeck, 2006).…”
Section: Clinical Implications Of Assumptionmentioning
confidence: 99%
“…[5][6][7] Early intervention for ASD in European countries is heterogeneous and poorly evaluated to date. 8 In French-speaking European countries, most children and their families have access to a public consultation centre specialised in autism. Families and children have regular consultations with a public psychologist or child and adolescent psychiatrist, but meeting schedules vary greatly (weekly, monthly or once a quarter).…”
Section: Introductionmentioning
confidence: 99%
“…Of all interventions, speech and language therapies are those most frequently reported. 8 These therapies can vary in frequency (30 min per session and up to four times per week). All these different treatments can be delivered in public or private centres.…”
Section: Introductionmentioning
confidence: 99%